Internally Generated Revenue (IGR) in Delta State: A Tool for Infrastructural Development - Sokoh, G. (Journal of Public Policy and Administration, 2023)
Purpose: The study examines internally generated revenue (IGR) in Delta State as a tool for infrastructural development. The Ordinary Least Squares was used to analyze the impact of internally generated revenue on infrastructural development in Delta State; the data used covered the period between 2008 to 2018. Methodology: The data was generated from a combination of publishing materials and data from Delta State Ministry of Finance Findings: The study findings indicate that the internally generated revenue has an insignificant impact on government expenditure on health. This indicates that the fund generated internally within the state has not improved the spending on the health infrastructure. On the contrary, on education infrastructure, the result indicates that the internally generally revenue by the Delta State Government has a significant impact on government expenditure on education infrastructure. This result indicates that the internally generated revenue from Delta State has improved the money spent on the educational infrastructure. Unique Contribution to Theory, Practice and Policy: Based on the findings, the researcher recommends that the government should spend at least 40 percent of the internally generated revenue in financing the health sector through improved budgetary provision. This will improve the development process in Delta State. The Delta State government should put in place measures to improve the total money generated internally by levying and collating appropriate taxes.